Dermatóglífos de mulheres obesas brasileiras - Pasetti, Sérgio R.; Gonçalves, Aguinaldo; Padovani, Carlos R. [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2012)
Study design: descriptive, observational, cross-sectional. Purpose: Obesity is a complex, multifactorial disease, including genetic and endocrine factors, demographic, socioeconomic, and epidemiological changes. It affects children, adults, and elderly persons. Searching respective hereditary risk indicators is increasing, mainly by applying simple and low-cost methodology. We included thus dermatoglyphics. Objective: To investigated 30 Brazilian women dermatoglyphic profiles, 46.1 ± 07.87 years old, and body fat % equal or higher than 30%. Results: Arch predominance, low loop frequency, and high amount of IV-finger whorls were observed, as well as frequency of rare palmar pattern in 2-interdigital area. Conclusions: Data confirm the variability of dermatoglyphics frequency in different population groups, revealing that the findings meant obesity, regardless of women's different personal characteristics. Thus, additional evidences on constitutional component of obesity have been accumulated.
Brazilian obese women dermatoglyphics
Keywords: Constitutionality; Dermatoglyphics; Obesity; Women; adult; body fat; Brazil; clinical article; controlled study; cross-sectional study; demography; descriptive research; endocrine function; epidemiological data; female; finger; finger dermatoglyphics; hand palm; health care cost; heredity; human; obesity; observational study; risk factor; social status